1999
DOI: 10.1021/bi9815896
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Inhibitors Specific for Bacterial Thymidylate Synthase,

Abstract: Thymidylate synthase is an attractive target for antiproliferative drug design because of its key role in the synthesis of DNA. As such, the enzyme has been widely targeted for anticancer applications. In principle, TS should also be a good target for drugs used to fight infectious disease. In practice, TS is highly conserved across species, and it has proven to be difficult to develop inhibitors that are selective for microbial TS enzymes over the human enzyme. Using the structure of TS from Lactobacillus cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…Human TS pharmacogenomics has been focused to 5' and 3' untranslated polymorphisms, tandem repeats, and also in mutations in the TS coding region (Barbour, Berger & Berger, 1990;Tong et al, 1998). Furthermore, TS stands as an important model to understand structure-function relationships and as a paradigm for structure based drug design against various bacterial and proliferative diseases (Stout et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Human TS pharmacogenomics has been focused to 5' and 3' untranslated polymorphisms, tandem repeats, and also in mutations in the TS coding region (Barbour, Berger & Berger, 1990;Tong et al, 1998). Furthermore, TS stands as an important model to understand structure-function relationships and as a paradigm for structure based drug design against various bacterial and proliferative diseases (Stout et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TS has been used a number of times to validate other methods of drug discovery. [148][149][150][151] Significantly, E. coli TS was used to generate an initial proof-of-concept for disulfide tethering by Erlanson et al [51] and was therefore considered to provide an excellent platform for proof-of-concept KTGT studies. Although TS has 5 native cysteine residues, in agreement with previous studies, [152] Erlanson et al demonstrated that only the catalytic cysteine (C146) is solvent exposed.…”
Section: Discussionmentioning
confidence: 99%
“…TS and DHFR are two of the most known target in anticancer chemotherapy and only recently TS has been regarded as potential target for anti-infectious diseases. [2][3][4][5][6][7][8][9][10][11][12] In anticancer chemotherapy, TS is strongly inhibited by the nucleotide substrate (dUMP) analog, 5-fluoro-2'-deoxyuridine monophosphate (FdUMP) and the folate substrate (mTHF, 5,10-methylenetetrahydrofolate) analogs, such as However severe resistance problems are encountered after prolonged administration of these drugs, owing to their high structural similarity to the folate cofactor. Many of the resistance mechanisms are related the fact that folate analogs drugs are metabolized through the same pathway that folate does.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new series of compounds, unrelated to mTHF, with TS inhibitory activity were discovered. 2,[7][8][9] In particular phenolphthalein (Pth, Figure 2), a well-known pH indicator, was identified in a pioneering work of structure-based drug design, in which an automated docking procedure (DOCK 3.0) was applied to the virtual screening of 55,313 compounds taken from the Fine Chemical Directory (FCD), against the three-dimensional structure of LcTS. 2 The compound shows an inhibition constant (K i ) of 4.4 µM against LcTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation